Mental health status, influencing factors and self-coping approaches among medical imaging students at International Islamic University Malaysia - Mohd Ghazali, Muhammad Putera Hakimi; Sohaimi, Norhanna; Kamarul Zaman, Fatihah Syafinaz; Amran, Umi Nadrah (IIUM Press, 2025)
Background: This research investigates the mental health status, influencing factors, and self-coping strategies among Medical Imaging students at the International Islamic University Malaysia (IIUM). Recognizing the increasing trend of mental health issues among students, this study aims to identify the prevalence of depression, anxiety, and stress, and to explore the factors contributing to these conditions. Methods: The study used a cross-sectional design. The target population was IIUM Medical Imaging students (Year 1 to Year 4). Convenience sampling was performed. The required sample size was 79, calculated using the Krejcie and Morgan method. A total of 88 completed questionnaires were returned. Data collection was conducted online from March to May 2024, using a newly designed questionnaire consisting of four parts, including the Depression, Anxiety, and Stress scale (DASS-21). Data analysis for the objectives will use descriptive analysis. Results: The findings revealed a high prevalence of mental health issues among the students, with significant levels of depression, anxiety, and stress reported. Key factors influencing mental health included academic workload, social support, financial difficulties, and gender differences. Male and female students exhibited different levels of mental health issues, with variations in the factors influencing their mental wellbeing. Furthermore, the study explored self-coping strategies employed by the students to manage their mental health challenges. Common self-coping approaches included engaging in religious activities, seeking support from family and friends, participating in recreational activities, and utilizing entertainment and art as stress relief methods. Notably, activities such as physical exercise, music, and nature walks were identified as effective in alleviating symptoms of depression, anxiety, and stress. Conclusion: The study underscores the critical need for increased awareness and interventions to address mental health issues among university students. It highlights the importance of providing adequate support systems and promoting effective self-coping mechanisms to improve the overall well-being and academic performance of students. The research contributes valuable insights into the mental health landscape of Medical Imaging students and offers recommendations for future studies and institutional policies to enhance student mental health support.